Coupling of Winter Climate Transitions to Snow and Clouds Over the Prairies - Betts, Alan K.; Desjardins, Raymond; Worth, Devon; Wang, Shusen; Li , Junhua (Emerging Issues in Environment, Geography and Earth Science Vol. 4, 2023)
Using data from 13 climate stations on the Canadian Prairies, together with opaque cloud cover and daily snow depth, to analyze the winter climate transitions with snow, we find that a snow cover acts as a fast climate switch. Surface temperature falls by about 10 K with fresh snowfall and rises by a similar amount with snowmelt, while the daily range of relative humidity falls to around 5–15% with snow cover. These are robust climate signals. For every 10% decrease in days with snow cover over the Canadian Prairies, the mean October to April climate is warmer by about 1.4 K. Stratifying by daily mean opaque cloud cover across snow transitions shows the rapid shift within 5 days from a diurnal cycle dominated by shortwave cloud forcing to one dominated by longwave cloud forcing. We calculate the change in the surface radiative budget with snow using surface albedo data from the Moderate Resolution Imaging Spectroradiometer and station longwave data. We find that with the fall-winter snow transitions, the surface radiative heating is reduced by 50Wm_2, with 69% coming from the reduced net shortwave flux, resulting from the increased surface albedo and a small increase in effective cloud albedo, and 31% from a reduced incoming longwave flux. This drop in surface radiative heating is sufficient to produce a drop in the surface radiometric skin temperature of 11 K. We find that in winter, the monthly mean diurnal climate is more closely coupled to the diurnal shortwave forcing than the mean diurnal climate.